2013
DOI: 10.1186/cc11933
|View full text |Cite
|
Sign up to set email alerts
|

Haloperidol prophylaxis in critically ill patients with a high risk for delirium

Abstract: IntroductionDelirium is associated with increased morbidity and mortality. We implemented a delirium prevention policy in intensive care unit (ICU) patients with a high risk of developing delirium, and evaluated if our policy resulted in quality improvement of relevant delirium outcome measures.MethodsThis study was a before/after evaluation of a delirium prevention project using prophylactic treatment with haloperidol. Patients with a predicted risk for delirium of ≥ 50%, or with a history of alcohol abuse or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 34 publications
0
64
1
2
Order By: Relevance
“…This effect was most pronounced in very high risk patients. A multicentre study on that strategy has just been completed and is awaiting final analyses [22]. Experiences from perioperative care in VOPs also suggest that preoperative prophylaxis with haloperiodol [23] and recently with dexmedetomidine [24] also may be effective.…”
Section: Deliriummentioning
confidence: 99%
“…This effect was most pronounced in very high risk patients. A multicentre study on that strategy has just been completed and is awaiting final analyses [22]. Experiences from perioperative care in VOPs also suggest that preoperative prophylaxis with haloperiodol [23] and recently with dexmedetomidine [24] also may be effective.…”
Section: Deliriummentioning
confidence: 99%
“…Since the lack of evidence about the efficacy of typical versus atypical antipsychotics, Ely et al are conducting the MIND-USA (Modifying the Impact of ICU-Induced Neurological Dysfunction-USA) Study (ClinicalTrials.gov Identifier NCT01211522) to define the role of this drugs in the management of delirium and on short- and long-term clinical outcomes in vulnerable critically ill patients (61). Delirium prophylaxis with medications is discouraged in the PAD guidelines, but recent small studies on delirium prophylaxis with antipsychotics showed that a low-dose of haloperidol may reduce the incidence of delirium in ICU patients (62, 63). By contrast, the HOPE-ICU randomized controlled trial showed no benefit of haloperidol administration for delirium prophylaxis in a mixed population of medical and surgical adult ICU patients (64).…”
Section: Deliriummentioning
confidence: 99%
“…Antipsychotic administration in the ICU is controversial (9, 19-21) and has not been studied in critically ill patients with subsyndromal delirium. One single-center, uncontrolled, before-after analysis suggested that the administration of haloperidol throughout the period of critical illness may reduce delirium and lower mortality (19).…”
Section: Introductionmentioning
confidence: 99%